Serum uric acid and fatal myocardial infarction: detection of prognostic cut-off values. Issue 3 (March 2020) - Casiglia, Edoardo; Tikhonoff, Valérie; Virdis, Agostino; Masi, Stefano; Barbagallo, Carlo M.; Bombelli, Michele; Bruno, Bernardino; Cicero, Arrigo F.G.; Cirillo, Massimo; Cirillo, Pietro; Desideri, Giovambattista; D'Elia, Lanfranco; et al.
Abstract : Objective: The Working Group on Uric Acid and Cardiovascular Risk of the Italian Society of Hypertension conceived and designed an ad-hoc study aimed at searching for prognostic cut-off values of serum uric acid (SUA) in predicting fatal myocardial infaction (MI) in women and men. Methods: The URic acid Right for heArt Health study is a nationwide, multicentre, observational cohort study involving data on individuals aged 18–95 years recruited on a regional community basis from all the territory of Italy under the patronage of the Italian Society of Hypertension with a mean follow-up period of 122.3 ± 66.9 months. Results: A total of 23 467 individuals were included in the analysis. Cut-off values of SUA able to discriminate MI status were identified by mean of receiver operating characteristic curves in the whole database (>5.70 mg/dl), in women (>5.26 mg/dl) and in men (>5.49 mg/dl). Multivariate Cox regression analyses adjusted for confounders (age, arterial hypertension, diabetes, chronic kidney disease, smoking habit, ethanol intake, BMI, haematocrit, LDL cholesterol and use of diuretics) identified an independent association between SUA and fatal MI in the whole database (hazard ratio 1.381, 95% confidence intervals, 1.096–1.758, P  = 0.006) and in women (hazard ratio 1.514, confidence intervals 1.105–2.075, P  < 0.01), but not in men. Conclusion: The results of the current study confirm that SUA is an independent risk factor for fatal MI after adjusting for potential confounding variables, and demonstrate that a prognostic cut-off value associated to fatal MI can be identified at least in women. Abstract : Supplemental Digital Content is available in the text